Perceived Ease of Use and Repurchase Intention: The Role of Customer Satisfaction in Mobile Banking - Muhamad Amir Ariandi; Renni Mayasari; Yunita Yunita; Aisyah Fajriantini; Rizky Zakariyya Rasyad (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study investigates the relationship between perceived ease of use and repurchase intention by considering customer satisfaction as a mediating variable among Livin’ by Mandiri users in Samarinda. The increasing adoption of digital banking has created intense competition, making it essential for banks to improve user experience in order to maintain customer loyalty. A quantitative research approach was applied using a survey method. Data were obtained from 100 respondents through an online questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The findings reveal that perceived ease of use does not directly influence repurchase intention. However, it has a significant positive impact on customer satisfaction, which subsequently affects repurchase intention. In addition, customer satisfaction functions as a full mediator in the relationship between perceived ease of use and repurchase intention. These results indicate that ease of use alone is insufficient to encourage continued usage unless it contributes to a satisfying user experience. Therefore, banks should prioritize enhancing overall user satisfaction alongside system usability to improve customer retention in digital banking services.